Vaccines as a preventive tool for substance use disorder: A systematic review including a meta-analysis on nicotine vaccines' immunogenicity - Roberto Scendoni; Emanuele Bury; Isabella Lima Arrais Ribeiro; Roberto Cameriere; Mariano Cingolani (Taylor & Francis Group, 2022)
The research on substance use disorders is ongoing in the quest to find anti-addiction vaccines to treat drug abuse. This article provides a systematic review of clinical trials that have been conducted on humans to evaluate the efficacy, safety, and abstinence rates of anti-addiction vaccines for different drugs, with useful results regarding cocaine and nicotine vaccines in particular; this study includes also a meta-analysis to establish the antibody-titer production following the nicotine vaccination, while a meta-analysis of cocaine vaccines was not performed due to the small number of included trials. The articles taken into consideration were published between 2002 and 2015, including searches through 2022. Overall, 13 articles were selected with 2,266 participants from different ethnic groups. The meta-analysis of nicotine vaccines showed that vaccinated groups were 50 times more likely to create specific antibodies compared to the non-vaccinated. These results demonstrated how the nicotine vaccine has good immunogenicity.